Optimalisasi maharah kalam melalui model pembelajaran komunikatif-interaktif di SMPIT Mutiara Insani Delanggu Klaten - Mahmudah, Iffah Ihyaa’ul; Putra, Sudarmadi; Widodo, Joko (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study aims to describe the optimization of students’ Arabic speaking skills (maharah kalam) through the implementation of a communicative-interactive learning model at SMPIT Mutiara Insani Delanggu Klaten in the 2024/2025 academic year. Using a descriptive qualitative approach, data were collected through classroom observation, in-depth interviews with teachers and students, and documentation analysis. The findings revealed that the use of communicative-interactive strategies, such as group discussions, role-playing, hiwar techniques, and contextual vocabulary cards, significantly improved students’ fluency and speaking confidence. Despite challenges such as limited background knowledge and low self-confidence, teachers overcame these issues by providing scaffolding and creating a supportive learning environment. This study highlights the importance of building a language-rich environment and developing thematic vocabulary to effectively enhance students’ Arabic speaking skills.